THE INVISIBLE LANDSCAPE OF ENERGY TRANSITIONS - Viviana Ferrario; Benedetta Castiglioni (Bollettino della Società Geografica Italiana, 2019)
The current transition to renewable energy, established within the frame of sustainable development policies, as it is known, is plagued by contradictions and opacity, stimulating a considerable debate over the last few years, in which landscape often occupies a significant role. The aim of this article is to critically explore the perspective of the landscape discourse in order to interpret the territorial transformations related to renewable energy in a broader way than merely focusing on aesthetics. In particular, it appears that reflecting on the invisible dimensions of the landscape can contribute to the debate. Thus, the attention is paid to some categories of invisible landscapes: the landscapes been deleted, buried, masked, removed or hidden; the projects remained without implementation; the reciprocal landscapes. The basin of the Piave river and its hydropower exploitation represents a case study aiming at testing the application of these categories to «unveil» the inherent contradictions of the relationship between renewable energy and sustainability.